ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK RESTORAN PADA DINS PENDAPATAN PENGELOLA KEUANGAN DAN KEKAYAAN DAERAH KABUPATEN TOBA SAMOSIR - Jenni Nova Yanti Siburian; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Tax is one of the main income sources for a country that is paid by the public. Restaurant tax is a mandatory fee charged to entities or persons for services selling food and / or beverages consumed by the purchaser either in the ministry or in another place with free of charge. Effectiveness research restaurant tax collection was conducted in Toba Samosir. The purpose of this study is to determine and analyze the effectiveness of Tax Collection Restaurant and to identify and analyze factors that influence the effectiveness of the Restaurant Tax Collection Revenue Service Financial Management and Wealth Toba Samosir regency. Based on the results of the Restaurant Tax Collection Effectiveness Analysis at the Department of Revenue Financial Management and Wealth Toba Samosir concluded